The Role of Nutrition in Maintaining Hormone Balance: Impact on Emotional Wellbeing - Sari, Desi Ratna (Journal Nutrizione, 2024)
Emotional well-being is crucial for leading a fulfilling life, encompassing mood stability, stress coping abilities, and positive interpersonal relationships. This state is intricately linked to hormonal balance within the body, where hormones regulate various emotional and psychological aspects. Disruption in hormonal equilibrium, often influenced by dietary factors, can lead to mood swings and difficulty in managing stress. Therefore, understanding the nexus between diet, nutrition, and hormonal balance is imperative for optimal emotional well-being. This paper delves into the relationship between nutrition and emotional health, emphasizing the impact of diet on hormonal regulation and subsequent emotional states. Through quantitative research involving 500 participants from diverse backgrounds, it was found that while most individuals possess basic nutrition knowledge, translating this into dietary practice remains a challenge. Consumption of fast food correlated with higher stress levels, while increased intake of fruits and vegetables was associated with lower stress levels. Interestingly, demographic factors such as age and gender did not significantly influence this relationship. Moving forward, interventions integrating nutrition education and behavioral strategies are crucial for promoting healthier dietary habits and enhancing emotional well-being in individuals